Preparation method of graphene-aluminum composite material for realizing strong interface bonding by controlling diffusion of Mg element through seepage effect of pressure infiltration
Through technical means such as pressure impregnation and ball milling, the diffusion and distribution of Mg elements in graphene-aluminum composite materials are controlled, which solves the problem of interfacial aggregate of Mg elements, and significantly improves the mechanical properties of the composite materials and the uniform distribution of Mg elements. .
Patent Information
- Application Number
- CN202411590797.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The Mg element in the aluminum alloy degenerates on the surface of graphene, resulting in the brittle phase Al4C3 on the interface, reducing the mechanical properties of the composite material. The interfacial degenerate of the Mg element reduces its uniform distribution in the matrix and reduces the precipitation strengthening effect.
The seepage effect of pressure impregnation is used to control the diffusion of Mg elements. Through ball milling and high-temperature sintering, graphene is uniformly dispersed on the aluminum surface to form a strong mechanical bond, and the formation of magnesium-aluminum spinel during the impregnation process. Inhibit the interface of Mg elements.
It effectively inhibits the interfacial aggregate of Mg elements, improves the mechanical properties of the composite material, including the improvement of tensile strength and elastic modulus, and maintains the uniform distribution of Mg elements in the matrix, enhancing the precipitation strengthening effect.
Smart Images

Figure CN119457055A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a graphene-aluminum composite material. Background Art
[0002] Aluminum alloy is a multifunctional material with light weight, high strength, excellent thermal and electrical conductivity, and is increasingly widely used in industrial production and daily life. Graphene, as a newly discovered two-dimensional material reinforcement, has received widespread attention since its advent. Graphene has extremely high theoretical performance. The theoretical tensile strength of graphene can reach 130GPa, and the hardness can reach 0.5-1TPa, which is several times that of diamond. It has a broad application prospect in the field of composite materials. Since the advent of graphene, it has been widely used in the field of composite materials. The graphene-pure aluminum composite material system has greatly improved the performance of pure aluminum composite materials. The yield strength and tensile strength of aluminum alloy are 2 to 3 times that of pure aluminum. Therefore, in order to meet the demand for high-strength and high-rigidity composite materials, in recent years, the research on composite materials of graphene and pure aluminum matrix has been gradually replaced by composite materials of graphene and aluminum alloy matrix. Composite materials with aluminum alloy as the matrix are expected to obtain higher mechanical properties, and the alloying elements in aluminum alloy may also be beneficial to control the reaction between graphene and aluminum matrix.
[0003] The Mg element in the aluminum alloy will segregate to the graphene surface, and the segregated Mg element will inhibit the formation of the brittle phase Al4C3 at the graphene-aluminum interface, thereby improving the mechanical properties of the composite material. However, the interface segregation of the Mg element causes the Mg element, which should be evenly distributed and play a precipitation strengthening role, to segregate to the interface of the graphene-aluminum composite material, reducing the content of the evenly distributed Mg element in the matrix, thereby reducing the precipitation strengthening effect of the Mg element. Therefore, there is an urgent need for a preparation method of a graphene-aluminum composite material that controls the interface segregation of the Mg element and compensates for the Mg content in the matrix. Summary of the invention
[0004] In order to solve the problem of Mg element segregation on the graphene surface, the present invention proposes a preparation method of a graphene-aluminum composite material that utilizes the seepage effect of pressure infiltration to control the diffusion of Mg element to achieve strong interface bonding, which can inhibit the interface segregation of Mg element and compensate for the Mg content in the matrix.
[0005] The method for preparing a graphene-aluminum composite material that utilizes the percolation effect of pressure infiltration to control the diffusion of Mg elements and realize strong interface bonding is carried out according to the following steps:
[0006] 1. Weighing
[0007] Weigh 1% to 3% of graphene and the remainder of aluminum alloy powder according to mass fraction; then weigh Mg metal, the mass of Mg metal being 3% to 10% of the total mass of graphene and aluminum alloy powder;
[0008] The Mg metal is a magnesium-aluminum alloy; pure Mg is prone to explosion and sputtering during the infiltration process, and pressure infiltration of magnesium elements into the preform by a magnesium-aluminum alloy is safer and less prone to explosion and sputtering;
[0009] 2. Graphene dispersion and preform molding
[0010] 60% of the aluminum alloy powder weighed in step 1 and all the graphene are mixed and ball-milled, the ball-milled mixed powder is loaded into a steel mold, and cold-pressed using a hydraulic press to obtain a composite material preform;
[0011] The ball-to-material ratio of the ball milling process is (8-20):1, the rotation speed is (150-250) r / min, and the ball milling time is 6 hours; the graphene can be evenly dispersed on the aluminum surface through ball milling, and the graphene and aluminum powder can form a strong mechanical bond through ball milling, thereby improving the strength of the composite material; the use of a larger ball-to-material ratio can make the graphene dispersed more evenly, while opening the graphene clusters, reducing the agglomeration of graphene on the aluminum surface, and reducing the large amount of aggregation of the brittle phase Al4C3 during subsequent sintering and infiltration processes; the appropriate rotation speed can obtain a material with better graphene dispersion effect, which will neither cause uneven dispersion nor breakage of the graphene;
[0012] 3. High temperature sintering of composite material preform
[0013] The composite material preform obtained in step 2 is placed together with the mold into an atmosphere furnace, the atmosphere furnace is first evacuated to a vacuum, and then a protective gas is introduced into the atmosphere furnace for high-temperature sintering to obtain a graphene-aluminum composite material ingot;
[0014] The high temperature sintering process is as follows: heating to 300-350°C at a heating rate of 3-10°C / min and keeping the temperature for 2-3h, then heating to 600-650°C at a heating rate of 3-10°C / min and keeping the temperature for 3-6h, applying a pressure of 100-200MPa to the composite material preform during the heating process, cooling with the furnace after sintering, and obtaining a graphene-aluminum composite material ingot; sintering under pressure can ensure that the grains of the composite material are fine and dense;
[0015] The protective gas is a mixed gas of N2 and NO;
[0016] Evacuating the atmosphere furnace to a vacuum can prevent the composite material preform from being oxidized during the heating process. The protective gas composed of N2 and NO introduces a small amount of oxygen, and a mixed film of aluminum nitride and aluminum oxide can be generated at the interface at high temperature, thereby increasing the interface bonding strength; the aluminum nitride and aluminum oxide generated at the grain boundary reduce the direct contact between graphene and Al, forming a protective interlayer to reduce the reaction between C-Al and thus reduce Al4C3; nitrogen can prevent the oxygen that may enter the atmosphere furnace during the heating process from oxidizing the preform, and the thermal conductivity of nitrogen is higher than that in vacuum, making the heat transfer more uniform, thereby improving the crystal growth behavior and reducing the uneven grain growth phenomenon; after nitrogen forms aluminum nitride at the interface, the combination of oxygen and aluminum is reduced, thereby reducing the accumulation of aluminum oxide at the grain boundary.
[0017] 4. Preparation of graphene-aluminum composites with strong interface bonding by pressure infiltration
[0018] The remaining aluminum alloy powder and all the Mg metal weighed in step 1 are mixed and melted to obtain a melt, and then the melt is infiltrated into a graphene-aluminum composite ingot by a short-time pressure infiltration process. After the melt solidifies, it is demolded at high temperature and then quenched. The mixed melting of the aluminum alloy powder and the Mg metal can improve safety on the one hand and prevent the explosion and sputtering of pure Mg during the pressure infiltration process, and on the other hand, Mg can form magnesium-aluminum spinel with Al during the pressure infiltration process. The magnesium-aluminum spinel has good chemical stability and thermal stability. When magnesium and aluminum combine to form magnesium-aluminum spinel, the position of magnesium atoms can be effectively fixed, thereby inhibiting the tendency of magnesium segregation, reducing the segregation of Mg, and making the distribution in the matrix more uniform.
[0019] The short-time pressure infiltration process is as follows: the preheating temperature of the preform is 640°C, the temperature of the infiltrated melt is 880°C, the infiltration pressure is 40-60KN, and the time is 5-15min;
[0020] 5. Solution aging treatment
[0021] The composite material after quenching in step 4 is subjected to a solution aging treatment, and the process is completed;
[0022] The process of the solution aging treatment is: keeping at 530° C. for 1 hour, then quenching, and keeping at 175° C. for 6 hours after quenching. The solution aging treatment makes the Mg element evenly distributed in the composite matrix and controls the interface segregation of Mg.
[0023] Principle and beneficial effects of the present invention:
[0024] 1. In the present invention, nitrogen is introduced during the hot sintering process in the atmosphere furnace. On the one hand, it can prevent the composite material from being oxidized by oxygen in the air. On the other hand, nitrogen atoms will generate aluminum nitride at the interface at high temperature, reducing the aggregation of Al4C3 brittle phase generated by the reaction of graphene and aluminum matrix at the interface, thereby strengthening the interface of the graphene-aluminum composite material.
[0025] 2. The present invention applies pressure to the composite material preform while sintering in an atmosphere furnace, which can refine the grains of the composite material, make the structure dense, and increase the interface bonding strength.
[0026] 3. The present invention adopts a short-time pressure infiltration process, preheats the prepared preform in advance, mixes and melts the weighed aluminum alloy ingot and magnesium block, pours the molten mixed metal liquid into the preform mold, and slowly infiltrates the mixed molten alloy liquid into the graphene-aluminum composite material ingot under the action of pressure. Under the action of infiltration (the melt fills into the preform under the action of pressure, and the flowing melt has a driving force), the Mg in the mixed liquid will be more evenly distributed to increase the Mg content in the matrix; through a short-time high-temperature infiltration process and quenching, the infiltration is completed before Mg segregates to the graphene interface, and after the infiltration is completed, the quenching and cooling are performed to reduce the Mg segregation, which can effectively control the interface segregation behavior of the Mg element, make the Mg element more evenly distributed, and have a significant strengthening effect. In addition, the generated magnesium-aluminum spinel improves the interface strength and also improves the strength of the matrix;
[0027] 4. The present invention further adds Mg element on the basis of aluminum alloy. The Mg element contained in the aluminum alloy plays a role in interface regulation. During the sintering process of the preform, it is segregated at the interface, inhibiting the formation of the brittle phase Al4C3, and improving the interface bonding strength of the composite material. The Mg element added during the pressure infiltration process plays a role in alloy element compensation. A small part of the Mg element is segregated at the interface, but more Mg elements remain in the matrix and are evenly distributed, playing a role in precipitation strengthening;
[0028] 5. The present invention adopts high-temperature demoulding after pressure infiltration, and then quenching is performed under the condition of a cold oil bath, so that the graphene-aluminum composite material can be quickly cooled, and a large amount of interface segregation of Mg elements is fully suppressed, and the Mg elements are retained in the matrix to the greatest extent to play a strengthening role;
[0029] 6. The preparation process of the present invention is simple and efficient, does not require a complicated deformation process, has a simple processing method, and has a low production cost. It has great application prospects for large-scale preparation of graphene-aluminum composite materials with strong interface bonding;
[0030] 7. The graphene-aluminum composite material prepared by the present invention has excellent mechanical properties, the tensile strength of the composite material can reach 550-650MPa, the elastic modulus exceeds 90GPa, and the elongation exceeds 13.5%. The preparation process of the composite material is safe and efficient, simple and pollution-free, and low-cost, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 SEM image of the composite material without Mg compensation and the distribution content of Mg element near graphene;
[0032] Figure 2 SEM image of the composite material with 5% Mg compensation added and the Mg element distribution content near graphene. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0034] Specific implementation method 1: In this implementation method, the preparation method of the graphene-aluminum composite material with strong interface bonding is carried out by controlling the diffusion of Mg element by the percolation effect of pressure infiltration according to the following steps:
[0035] 1. Weighing
[0036] Weigh 1% to 3% of graphene and the remainder of aluminum alloy powder according to mass fraction; then weigh Mg metal, the mass of Mg metal being 3% to 10% of the total mass of graphene and aluminum alloy powder;
[0037] The Mg metal is a magnesium-aluminum alloy;
[0038] 2. Graphene dispersion and preform molding
[0039] 60% of the aluminum alloy powder weighed in step 1 and all the graphene are mixed and ball-milled, the ball-milled mixed powder is loaded into a steel mold, and cold-pressed using a hydraulic press to obtain a composite material preform;
[0040] The ball-to-material ratio of the ball milling process is (8-20):1, the rotation speed is (150-250) r / min, and the ball milling time is 6 hours;
[0041] 3. High temperature sintering of composite material preform
[0042] The composite material preform obtained in step 2 is placed together with the mold into an atmosphere furnace, the atmosphere furnace is first evacuated to a vacuum, and then a protective gas is introduced into the atmosphere furnace for high-temperature sintering to obtain a graphene-aluminum composite material ingot;
[0043] The high-temperature sintering process is as follows: heating to 300-350°C at a heating rate of 3-10°C / min and keeping the temperature for 2-3h, then heating to 600-650°C at a heating rate of 3-10°C / min and keeping the temperature for 3-6h, applying a pressure of 100-200MPa to the composite material preform during the heating process, and cooling with the furnace after sintering to obtain a graphene-aluminum composite material ingot;
[0044] The protective gas is a mixed gas of N2 and NO;
[0045] 4. Preparation of graphene-aluminum composites with strong interface bonding by pressure infiltration
[0046] The remaining aluminum alloy powder and all the Mg metal weighed in step 1 are mixed and melted to obtain a melt, and then the melt is infiltrated into a graphene-aluminum composite ingot by a short-time pressure infiltration process, and after the melt solidifies, it is demolded at high temperature and then quenched;
[0047] The short-time pressure infiltration process is as follows: the preheating temperature of the preform is 640°C, the temperature of the infiltrated melt is 880°C, the infiltration pressure is 40-60KN, and the time is 5-15min;
[0048] 5. Solution aging treatment
[0049] The composite material after quenching in step 4 is subjected to a solution aging treatment, and the process is completed;
[0050] The process of the solution aging treatment is: keeping the temperature at 530° C. for 1 hour, then quenching, and keeping the temperature at 175° C. for 6 hours after quenching.
[0051] This embodiment has the following beneficial effects:
[0052] 1. In this embodiment, nitrogen is introduced during the hot sintering process in the atmosphere furnace. On the one hand, it can prevent the composite material from being oxidized by oxygen in the air. On the other hand, nitrogen atoms will generate aluminum nitride at the interface at high temperature, reducing the aggregation of Al4C3 brittle phase produced by the reaction of graphene and aluminum matrix at the interface, thereby strengthening the interface of the graphene-aluminum composite material.
[0053] 2. In this embodiment, pressure is applied to the composite material preform during sintering in an atmosphere furnace, so that the composite material grains can be refined, the structure can be dense, and the interface bonding strength can be increased.
[0054] 3. This embodiment adopts a short-time pressure infiltration process, preheats the prepared preform in advance, and mixes and melts the weighed aluminum alloy ingot and magnesium block, pours the molten mixed metal liquid into the preform mold, and slowly infiltrates the mixed molten alloy liquid into the graphene-aluminum composite material ingot under the action of pressure. Under the action of infiltration (the melt fills into the preform under the action of pressure, and the flowing melt has a driving force), the Mg in the mixed liquid will be more evenly distributed to increase the Mg content in the matrix; through a short-time high-temperature infiltration process and quenching, the infiltration is completed before Mg segregates to the graphene interface, and after the infiltration is completed, the quenching and cooling are performed to reduce the Mg segregation, which can effectively control the interface segregation behavior of the Mg element, make the Mg element more evenly distributed, and at the same time have a significant strengthening effect. In addition, the generated magnesium-aluminum spinel improves the interface strength and also improves the strength of the matrix;
[0055] 4. In this embodiment, Mg is further added to the aluminum alloy. The Mg contained in the aluminum alloy plays a role in interface regulation. During the sintering process of the preform, it is concentrated at the interface, which inhibits the formation of the brittle phase Al4C3 and improves the interface bonding strength of the composite material. The Mg added during the pressure infiltration process plays a role in alloy element compensation. A small part of the Mg element is concentrated at the interface, but more Mg elements remain in the matrix and are evenly distributed, which plays a role in precipitation strengthening.
[0056] 5. This embodiment adopts high-temperature demoulding after pressure infiltration, and then quenching is performed under the condition of a cold oil bath, so that the graphene-aluminum composite material can be quickly cooled, and a large amount of interface segregation of Mg elements is fully suppressed, and the Mg elements are retained in the matrix to the greatest extent to play a strengthening role;
[0057] 6. The preparation process of this embodiment is simple and efficient, does not require a complicated deformation process, has a simple processing method, and has a low production cost. It has great application prospects for large-scale preparation of graphene-aluminum composite materials with strong interface bonding;
[0058] 7. The graphene-aluminum composite material prepared in this embodiment has excellent mechanical properties, the tensile strength of the composite material can reach 550-650MPa, the elastic modulus exceeds 90GPa, and the elongation exceeds 13.5%. The composite material preparation process is safe and efficient, simple and pollution-free, and low-cost, and is suitable for large-scale production.
[0059] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the graphene described in step 1 is a few-layer graphene with an average sheet diameter of 100nm to 25μm and an average thickness of 0.5 to 30nm.
[0060] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that the average particle size of the aluminum alloy powder in step one is 8 to 20 μm.
[0061] Specific embodiment four: This embodiment differs from any of specific embodiments one to three in that the aluminum alloy powder described in step one is one or a combination of Al-Si alloy, Al-Si-Cu alloy, Al-Mg-Si alloy, Al-Cu-Mg alloy, Al-Zn-Cu alloy, Al-Zn-Mg-Cu alloy, Al-Si-Cu-Mg alloy.
[0062] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that the mass fraction of Si in the Al-Si alloy is 2% to 25%; the mass fraction of Si in the Al-Mg-Si alloy is 0.5% to 25%, and the mass fraction of Mg is 0.5% to 50%; the mass fraction of Si in the Al-Si-Cu alloy is 0.5% to 25%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Cu in the Al-Cu-Mg alloy is 0.5% to 53%, and the mass fraction of Mg is 0.5 %~38%; the mass fraction of Zn in Al-Zn-Cu alloy is 0.5%~55%, and the mass fraction of Cu is 0.5%~53%; the mass fraction of Zn in Al-Zn-Mg-Cu alloy is 0.5%~55%, the mass fraction of Mg is 0.5%~38%, and the mass fraction of Cu is 0.5%~53%; the mass fraction of Si in Al-Si-Cu-Mg alloy is 0.5%~25%, the mass fraction of Cu is 0.5%~53%, and the mass fraction of Mg is 0.5%~38%.
[0063] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 1 to 5 in that: the ball-to-material ratio in the ball milling process in step 2 is 10:1, the rotation speed is 150 r / min, and the ball milling time is 6 h.
[0064] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the pressure applied during the cold pressing process in step 2 is 50-70 KN, and the holding time is 5-20 min. Cold pressing is beneficial for obtaining a composite material with better organization and performance.
[0065] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the volume ratio of N2 and NO in step three is (1-3):1.
[0066] Specific embodiment 9: This embodiment is different from any one of specific embodiments 1 to 8 in that: the demoulding temperature in step 4 is 450°C to 550°C.
[0067] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that water-soluble quenching oil is used during quenching in step 4. The water-soluble quenching oil can cool the composite material faster and fully inhibit the diffusion and segregation of the Mg element.
[0068] Example 1
[0069] The method for preparing the graphene-aluminum composite material with strong interface bonding by controlling the diffusion of Mg element by the percolation effect of pressure infiltration in this embodiment is carried out according to the following steps:
[0070] 1. Weighing
[0071] Weigh 1% of graphene and the rest of 6061 aluminum alloy powder according to mass fraction; then weigh Mg metal, the mass of which is 5% of the total mass of graphene and aluminum alloy powder;
[0072] The graphene is a few-layer graphene with an average sheet diameter of 5 μm and an average thickness of 3 nm;
[0073] The average particle size of the aluminum alloy powder is 8 μm;
[0074] The Mg metal is AM60 magnesium-aluminum alloy;
[0075] 2. Graphene dispersion and preform molding
[0076] 60% of the aluminum alloy powder weighed in step 1 and all the graphene are mixed and ball-milled, the ball-milled mixed powder is loaded into a steel mold, and cold-pressed using a hydraulic press to obtain a composite material preform;
[0077] The ball-to-material ratio of the ball milling process is 10:1, the rotation speed is 150 r / min, and the ball milling time is 6 hours; the graphene can be evenly dispersed on the aluminum surface through ball milling, and the graphene and aluminum powder can form a strong mechanical bond through ball milling, thereby improving the strength of the composite material; a larger ball-to-material ratio can make the graphene dispersed more evenly, while opening the graphene clusters, reducing the agglomeration of graphene on the aluminum surface, and reducing the large amount of aggregation and generation of the brittle phase Al4C3 during subsequent sintering and infiltration; a suitable rotation speed can obtain a material with better graphene dispersion effect, which will neither cause uneven dispersion nor breakage of the graphene;
[0078] The pressure applied during the cold pressing process is 60KN, and the holding time is 10 minutes; cold pressing is conducive to obtaining a composite material with better organization and better performance;
[0079] 3. High temperature sintering of composite material preform
[0080] The composite material preform obtained in step 2 is placed together with the mold into an atmosphere furnace, the atmosphere furnace is first evacuated to a vacuum, and then a protective gas is introduced into the atmosphere furnace for high-temperature sintering to obtain a graphene-aluminum composite material ingot;
[0081] The high temperature sintering process is as follows: heating to 300°C at a heating rate of 4°C / min and keeping the temperature for 2h, then heating to 600°C at a heating rate of 4°C / min and keeping the temperature for 4h, applying a pressure of 100MPa to the composite material preform during the heating process, cooling with the furnace after sintering, and obtaining a graphene-aluminum composite material ingot; sintering under pressure can ensure that the grains of the composite material are fine and dense;
[0082] The protective gas is a mixed gas of N2 and NO, and the volume ratio of N2 to NO is 2:1;
[0083] Evacuating the atmosphere furnace to a vacuum can prevent the composite material preform from being oxidized during the heating process. The protective gas composed of N2 and NO introduces a small amount of oxygen, which can form a mixed film of aluminum nitride and aluminum oxide at the interface at high temperature, increasing the interface bonding strength; the aluminum nitride and aluminum oxide generated at the grain boundary reduce the direct contact between graphene and Al, forming a protective interlayer to reduce the reaction between C-Al and thus reduce Al4C3; nitrogen can prevent the oxygen that may enter the atmosphere furnace during the heating process from oxidizing the preform, and the thermal conductivity of nitrogen is higher than that in vacuum, making the heat transfer more uniform, thereby improving the crystal growth behavior and reducing the uneven grain growth phenomenon; after nitrogen forms aluminum nitride at the interface, the combination of oxygen and aluminum is reduced, thereby reducing the accumulation of aluminum oxide at the grain boundary. 4. Preparation of graphene-aluminum composite materials with strong interface bonding by pressure infiltration
[0084] The remaining aluminum alloy powder and all the Mg metal weighed in step 1 are mixed and melted to obtain a melt, and then the melt is infiltrated into a graphene-aluminum composite ingot by a short-time pressure infiltration process, and after the melt solidifies, it is demolded at high temperature and then quenched;
[0085] The demolding temperature is 500°C; the mixed melting of aluminum alloy powder and Mg metal can improve safety by preventing explosion and sputtering of pure Mg during pressure infiltration, and can also form magnesium-aluminum spinel with Al during pressure infiltration. Magnesium-aluminum spinel has good chemical stability and thermal stability. When magnesium and aluminum are combined to form magnesium-aluminum spinel, the position of magnesium atoms can be effectively fixed, thereby inhibiting the tendency of magnesium segregation, reducing Mg segregation, and making the distribution in the matrix more uniform.
[0086] The water-soluble quenching oil is used during quenching, so that the composite material can be cooled faster and the diffusion and aggregation of the Mg element can be fully suppressed;
[0087] The short-time pressure infiltration process is as follows: the preheating temperature of the preform is 640°C, the temperature of the infiltrated melt is 880°C, the infiltration pressure is 50KN, and the time is 10 minutes;
[0088] 5. Solution aging treatment
[0089] The composite material after quenching in step 4 is subjected to a solution aging treatment, and the process is completed;
[0090] The process of the solution aging treatment is: keeping the temperature at 530°C for 1 hour, then quenching, and keeping the temperature at 175°C for 6 hours after quenching. The solution aging treatment is performed to make the Mg element evenly distributed in the composite matrix and control the interface segregation of Mg;
[0091] Figure 1 SEM image of the composite material without Mg compensation (Mg metal was not added in the preparation process, and the rest was the same as in Example 1) and the distribution content of Mg element near graphene; Figure 2 Example 1 SEM image of the composite material with 5% Mg added as compensation and the distribution of Mg element content near graphene. According to the SEM images of the two composite materials, it can be seen that: Figure 1 There is indeed a large amount of Mg segregation at the graphene interface, but Figure 2 After Mg compensation, it can be seen that the number of graphene layers is less, and the Mg content in the matrix and at the interface is higher than that of the composite material without Mg compensation, proving that the addition of Mg metal plays a role in compensating the Mg element in the matrix of the composite material. The tensile strength of the graphene-aluminum composite material prepared in this embodiment reaches 609MPa, the elastic modulus reaches 94GPa, and the elongation is 14.5%; the composite material exhibits good tensile and elongation properties.
[0092] Example 2
[0093] The method for preparing the graphene-aluminum composite material with strong interface bonding by controlling the diffusion of Mg element by the percolation effect of pressure infiltration in this embodiment is carried out according to the following steps:
[0094] 1. Weighing
[0095] 3% of graphene and the rest of 6061 aluminum alloy powder were weighed according to mass fraction; Mg metal was then weighed, and the mass of Mg metal was 10% of the total mass of graphene and aluminum alloy powder;
[0096] The graphene is a few-layer graphene with an average sheet diameter of 5 μm and an average thickness of 5 nm;
[0097] The average particle size of the aluminum alloy powder is 10 μm;
[0098] The Mg metal is AM60 magnesium-aluminum alloy;
[0099] 2. Graphene dispersion and preform molding
[0100] 60% of the aluminum alloy powder weighed in step 1 and all the graphene are mixed and ball-milled, the ball-milled mixed powder is loaded into a steel mold, and cold-pressed using a hydraulic press to obtain a composite material preform;
[0101] The ball-to-material ratio of the ball milling process is 10:1, the rotation speed is 150 r / min, and the ball milling time is 6 h;
[0102] The pressure applied during the cold pressing process is 70KN, and the holding time is 10min;
[0103] 3. High temperature sintering of composite material preform
[0104] The composite material preform obtained in step 2 is placed together with the mold into an atmosphere furnace, the atmosphere furnace is first evacuated to a vacuum, and then a protective gas is introduced into the atmosphere furnace for high-temperature sintering to obtain a graphene-aluminum composite material ingot;
[0105] The high temperature sintering process is as follows: heating to 350°C at a heating rate of 5°C / min and keeping the temperature for 3 hours, then heating to 650°C at a heating rate of 5°C / min and keeping the temperature for 3 hours, applying a pressure of 150MPa to the composite material preform during the heating process, and cooling with the furnace after sintering to obtain a graphene-aluminum composite material ingot;
[0106] The protective gas is a mixed gas of N2 and NO, and the volume ratio of N2 to NO is 2:1;
[0107] 4. Preparation of graphene-aluminum composites with strong interface bonding by pressure infiltration
[0108] The remaining aluminum alloy powder and all the Mg metal weighed in step 1 are mixed and melted to obtain a melt, and then the melt is infiltrated into a graphene-aluminum composite ingot by a short-time pressure infiltration process, and after the melt solidifies, it is demolded at high temperature and then quenched;
[0109] The demoulding temperature is 500°C;
[0110] The quenching process uses water-soluble quenching oil;
[0111] The short-time pressure infiltration process is as follows: the preheating temperature of the preform is 640°C, the temperature of the infiltrated melt is 880°C, the infiltration pressure is 50KN, and the time is 10 minutes;
[0112] 5. Solution aging treatment
[0113] The composite material after quenching in step 4 is subjected to a solution aging treatment, and the process is completed;
[0114] The process of the solution aging treatment is: keeping at 530°C for 1 hour, then quenching, and keeping at 175°C for 6 hours after quenching. The tensile strength of the graphene-aluminum composite material prepared in this embodiment reaches 630MPa, the elastic modulus reaches 98GPa, and the elongation is 13.9%; the composite material shows good tensile and elongation properties.
Claims
1. A method for preparing a graphene-aluminum composite material with strong interface bonding by controlling the diffusion of Mg element through the seepage effect of pressure infiltration, characterized in that: The preparation method of the graphene-aluminum composite material with strong interface bonding by controlling the diffusion of Mg element by the percolation effect of pressure infiltration is carried out in the following steps:
1. Weighing Weigh 1% to 3% of graphene and the remainder of aluminum alloy powder according to mass fraction; then weigh Mg metal, the mass of Mg metal being 3% to 10% of the total mass of graphene and aluminum alloy powder; The Mg metal is a magnesium-aluminum alloy; 2. Graphene dispersion and preform molding 60% of the aluminum alloy powder weighed in step 1 and all the graphene are mixed and ball-milled, the ball-milled mixed powder is loaded into a steel mold, and cold-pressed using a hydraulic press to obtain a composite material preform; The ball-to-material ratio of the ball milling process is (8-20):1, the rotation speed is (150-250) r / min, and the ball milling time is 6 hours; 3. High temperature sintering of composite material preform The composite material preform obtained in step 2 is placed together with the mold into an atmosphere furnace, the atmosphere furnace is first evacuated to a vacuum, and then a protective gas is introduced into the atmosphere furnace for high-temperature sintering to obtain a graphene-aluminum composite material ingot; The high-temperature sintering process is as follows: heating to 300-350°C at a heating rate of 3-10°C / min and keeping the temperature for 2-3h, then heating to 600-650°C at a heating rate of 3-10°C / min and keeping the temperature for 3-6h, applying a pressure of 100-200MPa to the composite material preform during the heating process, and cooling with the furnace after sintering to obtain a graphene-aluminum composite material ingot; The protective gas is a mixed gas of N2 and NO; 4. Preparation of graphene-aluminum composites with strong interface bonding by pressure infiltration The remaining aluminum alloy powder and all the Mg metal weighed in step 1 are mixed and melted to obtain a melt, and then the melt is infiltrated into a graphene-aluminum composite ingot by a short-time pressure infiltration process, and after the melt solidifies, it is demolded at high temperature and then quenched; The short-time pressure infiltration process is as follows: the preheating temperature of the preform is 640°C, the temperature of the infiltrated melt is 880°C, the infiltration pressure is 40-60KN, and the time is 5-15min; 5. Solution aging treatment The composite material after quenching in step 4 is subjected to a solution aging treatment, and the process is completed; The process of the solution aging treatment is: keeping the temperature at 530° C. for 1 hour, then quenching, and keeping the temperature at 175° C. for 6 hours after quenching.
2. The method for preparing a graphene-aluminum composite material that utilizes the seepage effect of pressure infiltration to control the diffusion of Mg element and realize strong interface bonding according to claim 1, characterized in that: The graphene described in step 1 is a few-layer graphene with an average sheet diameter of 100nm to 25μm and an average thickness of 0.5 to 30nm.
3. The method for preparing a graphene-aluminum composite material using the seepage effect of pressure infiltration to control the diffusion of Mg element and realize strong interface bonding according to claim 1, characterized in that: The average particle size of the aluminum alloy powder in step 1 is 8 to 20 μm.
4. The method for preparing a graphene-aluminum composite material using the seepage effect of pressure infiltration to control the diffusion of Mg element and achieve strong interface bonding according to claim 1, characterized in that: The aluminum alloy powder described in step 1 is one of Al-Si alloy, Al-Si-Cu alloy, Al-Mg-Si alloy, Al-Cu-Mg alloy, Al-Zn-Cu alloy, Al-Zn-Mg-Cu alloy, Al-Si-Cu-Mg alloy, or a combination of several thereof.
5. The method for preparing a graphene-aluminum composite material that utilizes the percolation effect of pressure infiltration to control the diffusion of Mg element and realize strong interface bonding according to claim 4, characterized in that: The mass fraction of Si in the Al-Si alloy is 2% to 25%; the mass fraction of Si in the Al-Mg-Si alloy is 0.5% to 25%, and the mass fraction of Mg is 0.5% to 50%; the mass fraction of Si in the Al-Si-Cu alloy is 0.5% to 25%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Cu in the Al-Cu-Mg alloy is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%; the mass fraction of Zn in the Al-Zn-Cu alloy is 0.5% to 55%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Zn in the Al-Zn-Mg-Cu alloy is 0.5% to 55%, and the mass fraction of Mg is 0.5% to 38%, and the mass fraction of Cu is 0.5% to 53%; the mass fraction of Si in the Al-Si-Cu-Mg alloy is 0.5% to 25%, the mass fraction of Cu is 0.5% to 53%, and the mass fraction of Mg is 0.5% to 38%.
6. The method for preparing a graphene-aluminum composite material with strong interface bonding by controlling the diffusion of Mg element by the seepage effect of pressure infiltration according to claim 1, characterized in that: In step 2, the ball-to-material ratio of the ball milling process is 10:1, the rotation speed is 150 r / min, and the ball milling time is 6 h.
7. The method for preparing a graphene-aluminum composite material using the seepage effect of pressure infiltration to control the diffusion of Mg element and achieve strong interface bonding according to claim 1, characterized in that: The pressure applied during the cold pressing process in step 2 is 50-70 kN, and the holding time is 5-20 min.
8. The method for preparing a graphene-aluminum composite material with strong interface bonding by controlling the diffusion of Mg element by the seepage effect of pressure infiltration according to claim 1, characterized in that: In step 3, the volume ratio of N2 and NO is (1-3):
1.
9. The method for preparing a graphene-aluminum composite material using the seepage effect of pressure infiltration to control the diffusion of Mg element and achieve strong interface bonding according to claim 1, characterized in that: The demoulding temperature in step 4 is 450°C to 550°C.
10. The method for preparing a graphene-aluminum composite material with strong interface bonding by controlling the diffusion of Mg element by the seepage effect of pressure infiltration according to claim 1, characterized in that: During the quenching described in step 4, water-soluble quenching oil is used.
Citation Information
Patent Citations
Process for preparing SiC / Al electronic packaging materials by means of pressureless infiltration
CN102676901A
Graphene and light metal-based amorphous alloy particle co-reinforced magnesium alloy composite material and preparation method thereof
CN109207763A
Graphene / aluminum-matrix composite for high-speed impact resistance and preparation method thereof
CN109722556A
High-toughness aluminum-magnesium alloy composite material and preparation method thereof
CN117965973A
Manufacture of lightweight metal matrix composites with controlled structure
US20030133821A1